Retrospective analysis of commonly prevailing sexually transmitted diseases among transgender who attended outpatient clinic in Govt. Vellore Medical College from 2008-2015 - C., Dharmambal; A., Somasundaram; J., Balachander; R., Vasanthmoorthy (International Journal of Research in Dermatology, 2017)
Background: TGs are considered to constitute an important risk group for the transmission of Sexually Transmitted Infections (STIs) and Human Immunodeficiency Virus. High levels of STIs are predominant among TG sex workers due to unsafe sex practices. A study was conducted to describe the prevalence of sexually transmitted infection among Transgender who attended the outpatient clinic of Dermatoveneroleprology department for over 7 years and describe the contributing factors associated with sexually transmitted infections among transgender as there is a scarce data available about it. Methods: Retrospective study carried out on 123 transgender who attended the sexually transmitted disease clinic at Government Vellore Medical College and Hospital during the period 2008-2015. Results: Most of the transgender have active sexual life. 44% of them were having unprotected sex. Anal sex practice is more prevalent (88%). 25% reported one or other symptoms of sexually transmitted infection. 10.5% were reactive for syphilis and 11% reactive for HIV. Conclusions: A high reported prevalence of sexually transmitted infection exists despite many intervention policies adopted by the health system time to time. Implementation strategies to promote awareness among Transgender to access health care at the earliest time of appearance of symptoms and also periodical check-up may help to diagnose sexually transmitted infections at the early stage. Awareness and behavioral change on safe sex practices are the important needs in preventing sexually transmitted infections.